2019
DOI: 10.1108/tlo-01-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The ever-changing personality: revisiting the concept of triple-loop learning

Abstract: Purpose Considering personality as changeable through a bottom-up process of altering states, habits and traits, constitutes a shift in the predominant paradigm within personality psychology. The purpose of this paper is to reconsider Bateson’s theory of learning and organizational triple-loop learning in light of this recent empirical evidence. Design/methodology/approach This paper uses a multi-disciplinary conceptual approach. Based on an integrative analysis of literature from recent work in personality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…Fahrenbach et al suggested that deepening understanding of Bateson’s learning III theory is useful to operationalise triple-loop learning. 99 Furthermore, achieving triple-loop systemic learning requires a very important leadership commitment and momentum for change in depth 98 —leaders can provide a powerful role model of active learning that will help sustain an organisation’s efforts, through direct involvement that reflects coordination, vision and integration. 100 In addition, we believe that the institutionalisation of democratic governance mentioned above for double-loop learning is also essential for operationalising triple-loop systemic learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fahrenbach et al suggested that deepening understanding of Bateson’s learning III theory is useful to operationalise triple-loop learning. 99 Furthermore, achieving triple-loop systemic learning requires a very important leadership commitment and momentum for change in depth 98 —leaders can provide a powerful role model of active learning that will help sustain an organisation’s efforts, through direct involvement that reflects coordination, vision and integration. 100 In addition, we believe that the institutionalisation of democratic governance mentioned above for double-loop learning is also essential for operationalising triple-loop systemic learning.…”
Section: Discussionmentioning
confidence: 99%
“…This work will fully reflect triple-loop systemic learning if Guinea’s health system translates its findings into policy and practice (eg, creating a knowledge management unit within the MoH with representatives at regional and district levels), leading to the creation of new and well-organised learning structures/processes/strategies. Fahrenbach et al suggested that deepening understanding of Bateson’s learning III theory is useful to operationalise triple-loop learning 99. Furthermore, achieving triple-loop systemic learning requires a very important leadership commitment and momentum for change in depth98—leaders can provide a powerful role model of active learning that will help sustain an organisation’s efforts, through direct involvement that reflects coordination, vision and integration 100.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on our findings, we believe that contextual and environmental aspects are highly relevant for the organizational unlearning process. Furthermore, some interviewees stressed that knowledge, even if outdated and should be subject to change, may play a key role in the organization’s identity (Fahrenbach and Kragulj, 2019). This relates to Tsang (2008), who observed that a routine can be more or less socially embedded.…”
Section: Discussionmentioning
confidence: 99%
“…This implication for practitioners’ paper is based on Issue 6 from the previous 2022 volume. The articles from Issue 6 explored training transfer (Andoh et al, 2022), team diversity and humour (Batt-Rawden & Traavik, 2022), knowledge exchange and knowledge hiding (Kucharska and Rebelo, 2022), research on stability of personality traits and its relation to triple-loop learning (Fahrenbach & Kragulj, 2022), as well as case studies on interorganisational learning (Pareliussen et al, 2022) and strategic alliances (Ferrigno et al, 2022). The Issue 6 concludes with a Wraae (2021) book review exploring entrepreneurship education (Fust, 2022).…”
mentioning
confidence: 99%